PRMT5 genetic interactions with DNA double strand break repair genes - Hunter J. Bliss; Juliana Tron; Wesley Bush; Renee A. Bouley; Ruben C. Petreaca (PLoS ONE, 2025)
Protein arginine methyltransferase 5 (PRMT5) has pleiotropic functions in human cells but also participates in orchestrating DNA double strand break (DSB) repair. It methylates the TIP60 histone acetyltransferase complex to facilitate recruitment to the DSB and chromatin remodeling. PRMT5 mutations affect DSB repair by homologous recombination and increase chromosomal instability. In this report we characterized genetic interactions between PRMT5 mutations and mutations in other components of DSB repair pathway. We used data deposited on the Catalogue of Somatic Mutations in Cancers (COSMIC). We found that PRMT5 makes negative genetic interactions with TIP60 and member of the 9-1-1 complex (RAD9, RAD1, HUS1) which is required for checkpoint activation. A comprehensive analysis of all cancer data deposited on COSMIC reveals very few samples with mutations in both PRMT5 and TIP60 or components of the 9-1-1 complex in samples where mutations in other DNA damage repair genes occur (e.g., MRN, checkpoint genes, etc). This suggests that when more factors of the DNA damage repair machinery are destabilized, the functions of TIP60 and 9-1-1 appear to become essential. Protein 3-D structure analysis shows that mutations affect protein-protein interactions that may destabilize 9-1-1 or TIP60 complex formation. These data highlight interesting interactions between the various genetic pathways governing DSB repair. It also reveals potential therapeutic targets. For example, inhibition of the 9-1-1 complex in a PRMT5 mutant may selectively kill the cell. Given that PRMT5 small molecule inhibitors are being developed or already deployed, these findings should inform potential applications of these drugs.